Seismic vulnerability of power transformer bushings: Complex structural dynamics and seismic amplification. (1st May 2018) - Bender, Jon; Farid, Arvin
Abstract: While it is accepted that high voltage bushings mounted on power transformers receive amplified seismic loads due to the structural dynamics of the transformer tank, it is also the case that complex structures made from steel plates and frames often exhibit unpredictable dynamic behavior. Empirical and numerical studies have shown that many transformer designs produce bushing amplifications within the standard expected value of 2.0 times the load imposed on a rigid-mounted bushing. This 2x amplification is required for seismic testing according to IEEE (the Institute of Electrical and Electronics Engineers), and yet this same body of data has also shown that many designs impose greater dynamic amplification. This paper is a numerically-based case study of four power transformer bushing configurations. The study adds additional evidence that bushing amplifications greater than 2.0 are possible, and it demonstrates that the complexity of these systems makes generalization of design recommendations problematic.